Human resource management practices in the context of rising right‐wing populism. (3rd February 2020) - Cumming, Douglas J.; Wood, Geoffrey; Zahra, Shaker A.
Abstract: We review the relationship between the causes and impact of rising right‐wing populism and human resource management practice, drawing on the recent experiences of the United States and the United Kingdom. Specifically, we explore the links between right‐wing populism and firms and their HRM practices. Although the links between declining standards of work, employment, and populism may be indirect and spatially uneven, each impacts the other in a manner that reinforces existing trends. We pay particular attention to migration and labour mobility, pay dispersion, and job and occupational security. At the level of the workplace, the populist turn undermines workforce diversity and makes transnational mobility more difficult. At the same time, structural pressures mitigating against a greater commitment to employees and their development and well‐being contribute to a general climate of insecurity, which, in turn, reinforces populism.